2008
DOI: 10.1128/aac.00050-08
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective and Nonlinear Intestinal Absorption of Eflornithine in the Rat

Abstract: This study aimed to investigate if the absorption of the human African trypanosomiasis agent eflornithine was stereospecific and dose dependent after oral administration. Male Sprague-Dawley rats were administered single doses of racemic eflornithine hydrochloride as an oral solution (750, 1,500, 2,000, or 3,000 mg/kg of body weight) or intravenously (375 or 1,000 mg/kg of body weight). Sparse blood samples were obtained for determination of eflornithine enantiomers by liquid chromatography with evaporative li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In rat liver, L-eflornithine (L-difluoromethylornithine) was more effective in irreversibly inhibiting ornithine decarboxylase than D-eflornithine (D-difluoromethylornithine) (128). The mean bioavailability of L-and D-eflornithine in rats was 41% and 62%, respectively, indicating that eflornithine exhibits enantioselective absorption, the more potent L-isomer being less favoured (129).…”
Section: Eflornithinementioning
confidence: 98%
See 2 more Smart Citations
“…In rat liver, L-eflornithine (L-difluoromethylornithine) was more effective in irreversibly inhibiting ornithine decarboxylase than D-eflornithine (D-difluoromethylornithine) (128). The mean bioavailability of L-and D-eflornithine in rats was 41% and 62%, respectively, indicating that eflornithine exhibits enantioselective absorption, the more potent L-isomer being less favoured (129).…”
Section: Eflornithinementioning
confidence: 98%
“…Conflict and sociopolitical instability are associated with the persistence and resurgence of infection (62). There is some evidence that people develop immunity to T. b. gambiense (129), and it has been suggested that the inter-epidemic intervals observed in the twentieth century occurred while the population of susceptible individuals was increasing to a size that could support another epidemic.…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2007 the WHO, with funding from the sanofi-aventis programme, has provided eflornithine in kits including all necessary ancillary materials (Priotto et al 2008), but considerable logistic constraints remain as the kit for two patients has a volume of about 1 m 3 . An oral formulation was thought to solve many of the treatment related difficulties, but was abandoned after discouraging results of a pharmacokinetic trial (Na-Bangchang et al 2004;Jansson et al 2008).…”
Section: E F L O R N I T H I N Ementioning
confidence: 99%
“…d/l-DFMO was intravenously administered to a rat with a dosage of 375 mg/kg body weight (Sprague-Dawley rat, male, weighing approximately 300 g) [31]. The administered dose corresponds to a human dose of approximately 75 mg/kg.…”
Section: Biological Applicationmentioning
confidence: 99%